Mechanism and simulation analysis of cross-regional vegetable production and marketing docking in big cities based on evolutionary game - Na Wang; Fangru Liu; Lei Zhang (Frontiers in Sustainable Food Systems)
Non-local vegetables have become a crucial source of vegetable supply for major cities, establishing stable production-marketing linkage mechanisms between large cities and external vegetable-producing regions is now imperative. Existing research has primarily examined, from a static perspective, the mechanisms by which government interventions influence the cross-regional alignment of agricultural production and marketing, yet it has not explored the dynamic characteristics and evolutionary patterns that emerge in the cross-regional integration of vegetable supply chains. This paper aims to establish a stable and healthy cross-regional vegetable production and sales docking mechanism. Based on evolutionary game theory, it constructs a tripartite evolutionary game model involving “government guidance—farmer participation—wholesaler operation” to explore the behavioral strategies and mutual influence mechanisms of the three parties. Through simulation analysis, the study investigates the impact of these three parties on the efficient and stable operation of the cross-regional production, and sales docking chain. The research results show that the level of government support and subsidies for wholesalers and farmers influence the strategic behavior of wholesalers and farmers. Appropriate supervision and penalties are conducive to the consistency of decision-making behavior between the government and wholesalers, while excessive supervision and penalties can lead to increased costs that wholesalers cannot bear, resulting in non-responsive behavior from wholesalers and causing a vicious cycle in the operation of the production and sales docking chain. A key contribution of this paper lies in its application of an evolutionary game model to describe the decision-making processes and adaptive learning behaviors of the three principal actors—government, wholesalers, and farmers—throughout the cross-regional production—marketing integration process, and to trace their dynamic evolution over time. By framing these interactions under conditions of bounded rationality, the model both analyzes and predicts the collective strategies that emerge among stakeholders, thereby furnishing essential theoretical insights for strengthening integration and securing vegetable supply. In doing so, it extends existing agricultural supply theory and offers actionable guidance for orderly production planning in major vegetable—producing regions and for accurately aligning output with primary consumption markets.